Assessing the Effectiveness of the Module ’Embracing Non-Fiction: Essay Made Easy on the Essay Writing Performance of Grade 10 Learners - Curimatmat, Rochen Grace (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the effectiveness of the researcher-developed module “Embracing Non-Fiction: Essay Made Easy” in improving the essay writing performance of Grade 10 Leeuwenhoek learners at Dologon National High School during the academic year 2025–2026. Anchored on the Cognitive Process Theory of Writing, Constructivist Learning Theory, and the Input–Process–Output Model, the study used a quasi-experimental pre-test–post-test design with a descriptive component. Thirty Grade 10 learners were included through complete enumeration. The study utilized an essay writing test, the instructional module, a standardized writing rubric, and a perception survey questionnaire. Results showed that before the intervention, most learners were at the Developing level, while after the module implementation, most reached the Proficient level, with some achieving Outstanding performance. The paired sample t-test revealed a significant improvement from the pre-test mean score of 15.07 to the post-test mean score of 18.33, with a mean gain of 3.27 points and a result of t(29) = 7.53, p < 0.001. Learner perceptions were also highly positive, with most responses marked Agree or Strongly Agree in terms of clarity, usefulness, and engagement. The study concluded that the module effectively improved essay writing performance and recommended its integration or adaptation in Grade 10 English instruction. The study supports SDG 4 – Quality Education by promoting literacy, academic writing competence, and learner-centered instruction. Its sustainability impact lies in strengthening educational and institutional practices through structured, accessible, and context-responsive instructional materials.